Isolamento de células-tronco mesenquimais da medula óssea - De Camargo Bittencourt, Renata Aparecida [UNESP] (2006)
Mesenchymal Stem Cells (MSCs) have a high ability to renew and differentiate themselves into various lineages of conjunctive tissues. This study aimed to isolate the MSCs from murine bone marrow by using two different growth media and to characterize them with immunostaining with antivimentin antibody. We used six 2-week old BALB/c mice. Bone marrow was collected from mice's tibial and femoral channels and re-suspended in a final strength of 6x105 in Knockout-DMEM and high-glucose-DMEM media, supplemented by 10% FBS, and kept in a humidified 5% CO2 incubator at 37°C for 72 h, when non-adherent cells were removed during the change of medium. The number and density of adherent fibroblast-like colonies was greater with the Knockout-DMEM medium (within 5 days of culture) versus 10-20 days in DMEM-high glucose to get the same cellular concentration. The cells in both groups were highly positive for antivimentin antibody, characterizing them as MSCs. Obtaining MSCs as quickly as possible is essential for cell therapy field, especially when those cells are intended to be used for the repair of tissues from mesenchymal sources.